Electrodeposited polyethylenedioxythiophene with infiltrated gel electrolyte interface: a close contest of an all-solid-state supercapacitor with its liquid-state counterpart - Anothumakkool, Bihag; Torris, Arun A. T.; Bhange, Siddheshwar N.; Badiger, Manohar V.; Kurungot, Sreekumar (Nanoscale, 2014)
We report the design of an all-solid-state supercapacitor, which has charge storage characteristics closely matching that of its liquid-state counterpart even under extreme temperature and humidity conditions. The prototype is made by electro-depositing polyethylenedioxythiophene (PEDOT) onto the individual carbon fibers of a porous carbon substrate followed by intercalating the matrix with polyvinyl alcohol-sulphuric acid (PVA-H2SO4) gel electrolyte. The electrodeposited layer of PEDOT maintained a flower-like growth pattern along the threads of each carbon fiber. This morphology and the alignment of PEDOT led to an enhanced surface area and electrical conductivity, and the pores in the system enabled effective intercalation of the polymer-gel electrolyte. Thus, the established electrode-electrolyte interface nearly mimics that of its counterpart based on the liquid electrolyte. Consequently, the solid device attained very low internal resistance (1.1 Omega cm(-2)) and a high specific capacitance (181 F g(-1)) for PEDOT at a discharge current density of 0.5 A g(-1). Even with a high areal capacitance of 836 mF cm(-2) and volumetric capacitance of 28 F cm(-3), the solid device retained a mass-specific capacitance of 111 F g(-1) for PEDOT. This is in close agreement with the value displayed by the corresponding liquid-state system (112 F g(-1)), which was fabricated by replacing the gel electrolyte with 0.5 M H2SO4. The device also showed excellent charge-discharge stability for 12 000 cycles at 5 A g(-1). The performance of the device was consistent even under wide-ranging humidity (30-80%) and temperature (-10 to 80 degrees C) conditions. Finally, a device fabricated by increasing the electrode area four times was used to light an LED, which validated the scalability of the process.

Efficient Ag-nanoparticle embedded semi-IPN hydrogel for catalytic applications - Patwadkar, Manjusha V.; Gopinath, Chinnakonda S.; Badiger, Manohar V. (RSC Advances, 2015)
Silver nanoparticle embedded semi-IPN hydrogels based on a combination of poly(acrylamide) and poly(aspartic acid) were synthesized. These semi-IPN hydrogel networks can potentially serve as micro or nano reactors for entrapment of metal nanoparticles. Current methodology allows us to entrap metal nanoparticles throughout hydrogel networks via poly(aspartic acid) chains which are dispersed homogeneously in the gel matrix. The Ag-NPs were characterized by UV-vis absorption spectroscopy, transmission electronic microscopy (TEM), X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDAX). The Ag embedded hydrogels catalyze the reduction of 4-nitrophenol to 4-aminophenol in the presence of NaBH4 very efficiently at room temperature with good recyclability upto 3 cycles.

Enhanced drug release by selective cleavage of cross-links in a double-cross-linked hydrogel - Tiwari, Neha; Badiger, Manohar V. (RSC Advances, 2016)
In the present paper, we report on the synthesis and characterization of redox sensitive double-cross-linked poly(acrylic acid) hydrogels using two different cross-linking agents, Jeffamine (R) and cystamine. The amount of two cross-linking agents was varied in order to synthesize hydrogels with different mechanical strengths. Jeffamine provides mechanical stability to the hydrogels while cystamine incorporates redox sensitivity. The stress values at the break point of the mono-and double-crosslinked hydrogels were determined from stress-strain plots. The disulphide bonds (S-S) in the cystamine were cleaved selectively in the presence of dithiothreitol, which increased the degree of hydrogel swelling. This phenomenon of in situ breaking of one cross-linking and increasing the swelling ratio could be used in swelling-controlled drug delivery systems. The implication of selective breaking of cross-links on the swelling-controlled release of the anticancer drug doxorubicin was demonstrated. We also successfully prepared Ag nanoparticles in the dual cross-linked hydrogels in order to incorporate antibacterial properties and studied their release by selective cleavage of cystamine bonds. These double-cross-linked hydrogels show great promise in drug delivery and tissue engineering applications.

Electrospinning of non-ionic cellulose ethers/polyvinyl alcohol nanofibers: characterization and applications - Wali, Ashwini; Zhang, Yucheng; Sengupta, Poulomi; Higaki, Yuji; Takahara, Atsushi; Badiger, Manohar V. (Carbohydrate Polymers, 2018)
The morphology of spin-coated films and electrospun fibers of ethyl hydroxy ethyl cellulose (EHEC), hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) and their blends with Poly(vinyl alcohol) (PVA) was examined by AFM, SEM and contact angle measurements. These polysaccharides upon blending with PVA exhibited smooth surface which was evidenced by Atomic Force Microscopy (AFM) observation. The electrospinnability of above polysaccharides with PVA was demonstrated for the first time. The oriented fibers could be obtained using a rotating disc collector. Contact angles of spin-coated films and electrospun fibers were discussed in terms of hydrophobicity and wetting characteristics. Further, The nanofibers of EHEC/PVA were in-situ crosslinked using citric acid and were used for controlled release of an antibacterial drug, Chlorhexidine Digluconate (ChD). In-vitro studies of cytotoxicity, cell growth and cell proliferation were performed using L929 mouse fibroblast cells. These nanofiber mats show potential in drug delivery and as scaffolds in tissue engineering applications.
Keywords: cellulose; drug delivery; electrospinning; Ethyl hydroxy ethyl cellulose; Hydrophobically modified ethyl hydroxy ethyl; scaffold; Spin coating